Révolution et politique de la culture à Sharjah, 1979-2009 - Alexandre Kazerouni (Université de Provence, 2017)
More than a decade before the creation of new cultural platforms with a high level of international visibility in Qatar, Abu Dhabi and Dubai, with projects such as the Museum of Islamic Art in Doha, the Louvre Abu Dhabi or the Art Dubai fair, the ruler of Sharjah announced a « Revolution of Culture » for his emirate in 1979. A cultural policy was born out of it with a book fair, theatre, the fine arts and higher education as its fundamental pillars. This article studies this cultural policy between 1979 and 2009 with a focus on its ideological orientation, which is unusual for that period of time : Nasserist panarabism, then on its decline in the rest of the Arab world. This choice is linked to both the historical trajectory of the local ruling family, the Qawāsim, and to a policy of containment of Saudi cultural influence among the local youth through salafism.